EFEK GAYA ANTAR PARTIKEL DAN DIAMETER PARTIKEL TERHADAP KECEPATAN MINIMUM FLUIDISASI - Irhan Febijanto (Badan Pengkajian dan Penerapan Teknologi, 2009)
In this study, the effect of diameter particle and the effect of inter-particlecohesion force due to liquid bridge formation on the minimum fluidization velocityin the fluidized bed have investigated. Also the effect of inter-particle cohesionforce on a fluidization condition of the bed has observed by video camera. Theinvestigation results showed bigger diameter can give higher minimumfluidization velocity, and stronger inter-particle force can give higher minimumfluidization velocity, and then make a quality of fluidization of bed lower. Usingwith this investigation results, the mechanism of fouling and slaggingphenomena, which are happen in the coal-fired boiler can be explained.Kata kunci: fluidized bed, minimum fluidization velocity, particle diameter,relative humidity, inter-particle cohesion force